EVALUASI KINERJA PEMBANGKIT HIDROGEN SUBSTITUSI LNG REFORMER UNTUK PROSES PENCAIRAN BATUBARA BANKO - Danu Sumitro; Dhani Avianto Sugeng (Jurnal Energi dan Lingkungan (Enerlink), 2005)
Three entrained gasification processes have been investigated to produce hydrogen for direct liquefaction of Banko coal and compared with steam reforming of natural gas. They are Texaco gasification (USA), Prenflo process (Germany) and Hycol process(Japan). Despite some similarities, those gasification technologies also have some differences in their coal feed systems.The slurry feed system is adopted in the Texaco process, while Prenflo and Hycol processes are using dry feed system. Economic assessment shows that in the case of hydrogen generation from natural gas, hydrotreated liquefied oil of 125,000 bbl/d can be produced from 32,810 ton/d Banko coal (dry basis) and 7.2x106Nm3/d natural gas. In case of hydrogen generation from coal, coal consumption will increase by 19,600 ton/d and no natural gas is required. Besides the hydrotreated liquefied oil increases up to 7,800 bbl/d to become 133,400 bbl/d, the process also produces 1,520 ton/d gas fuel to be sold. In terms of energy efficiency, there is a production decline of 65.7% in case of hydrogen generation through gasification compared to steam reforming (68.0%).Kata kunci: Direct liquefaction, banko coal, hydrogen generation, gasification